Necesidad De Reforma El Art. 851 Del Código Civil, En Relación A La Ampliación De Las Causas De Extinción Del Patrimonio Familiar - Bravo Rodríguez, Alexandra Elizabeth (2015)
The family is the foundation of society, it is in need of such protection to protect it and to start with a guaranteed subsistence sufficiency and continuity. This has to have a heritage. Homestead is an Institution of Social Law, aimed at maintaining family unity, safeguard everyone, as a synonym of peace and economic stability for both social justice and high time that the Ecuadorian Legislator believes modern legal systems, laws clear, flexible limitations and new directions of law, establishing new causes of extinction and subrogation, in line with the current situation of the country and instituting and beneficiaries, restoring what was originally a social law. The Homestead was established in order to protect social and economically to the constituent and his family. Institution is established in the Constitution of the Republic, the Civil Code and other special laws, legal bodies containing rules, that despite the constant change of society, the very posing new requirements for legal, social, economic type, political, etc., have not yet been refurbished by the Ecuadorian Legislator, which has caused more of a problem of social legal, all this because there loopholes in the case of the extinction of Homestead since due to the progress of society are other justifiable grounds to be taken into account for the extinction of Homestead such as: - When required mortgage the real estate secured with Family Heritage for credit exclusively for improvements to the property. - When on account of poor health, the owner of the property constituted Homestead is his wish to donate the property to the beneficiaries of Homestead. - When Family Heritage subrogation is sought for future real property. - In cases of imperative and justified or urgent need indisputable advantage and usefulness to constituents and beneficiaries. Homestead lost from my point of view its rationale, for not conforming to legal and social reality of the constituent, because the rules currently governing the institution of Homestead both extinction unresponsive to our reality social, the same that has dabbled in a globalized world, it is important to the study and analysis of the problem, the same as not only part of a local reality but welcomes all Ecuadorian society.